The effect of behaviorally anthropomorphic service robots on customers’ variety-seeking behavior: an analytical examination of social presence and decision-making context - Wenchao Liu; Xin Xin; Chenyu Zheng (Frontiers in Robotics and AI)
The concept of anthropomorphism is crucial in enhancing interactions between service robots and humans, serving as a key consideration in the design of these robots. Nevertheless, the specific mechanisms by which the anthropomorphic traits of service robots influence customer behavioral responses remain inadequately understood. Furthermore, the incorporation of anthropomorphic robotic technology into customer service operational strategies presents a significant challenge for businesses. To explore the underlying mechanisms through which the anthropomorphic characteristics of service robots impact customer acceptance, this study conducted a series of six experiments to empirically test the proposed hypotheses. The empirical findings indicate notable differences in customer switching behaviors and selection quantity metrics, which can be linked to service contexts characterized by varying degrees of behavioral anthropomorphism. Additionally, social presence has been identified as a mediating variable that affects the relationship between the anthropomorphism of service robot behavior and its influence on customer variety-seeking behavior. The situational context of customer decision-making is also found to moderate the relationship between social presence and variety-seeking behavior. Consequently, it is recommended that service organizations implement service robots with diverse anthropomorphic features to enhance customer acquisition, cultivate loyalty, and improve overall marketing effectiveness.